BIOFILM FORMATION AND ANTIBIOTIC SUSCEPTIBILITY OF STROKE PATIENT’S URINARY CATHETER ISOLATES AT BETHESDA HOSPITAL, YOGYAKARTA - Christofer Sathya Wijaya Budi Sarwono (Berkala Ilmiah Kedokteran Duta Wacana, 2019)
Background: Antibiotic resistance currently challenges infectious disease management, specifically in combating biofilm formation. Biofilm might be developed on urinary catheter, in which stroke patients with urinary tract problem have higher risk of catheter associated urinary tract infection and problems related to antibiotic resistance. Aim: This study describes the microbe types from catheter isolates, measuring the antibiotic susceptibility and biofilm formation, especially in stroke patients at Bethesda Hospital, Yogyakarta. Method: This is a cross-sectional study, describing findings of specimens from stroke patients at Bethesda Hospital, since December 2018 to January 2019. The isolates were identified with standard method, the antibiotic susceptibility were tested with antibiotic disc on MHA medium, and the biofilm formation were assessed using tissue culture plate method. All procedure were done in Microbiology Laboratorium, FK UKDW. Result: Thirty three microbes were isolated from 30 specimens of urinary catheter (63,3% male, 36,3% female). There is 76% isolates incapable of developing biofilm, while 15% is moderate biofilm producer and 9% is strong biofilm producer. The susceptibility test showed 100% resistancy of ampicillin-sulbactam, tetracyclin, ketoconazole, itraconazole, and terbinafine. Around 50% of E. coli and 57% of K. pneumonias isolates is MDR, and 75% of A. baumanii is XDR. Conclusion: Isolated microbes from urinary catheter of stroke patients at Bethesda Hospital is dominated by E. coli, K. pneumoniae, and A. baumanii. Some of the microbes could form strong biofilm, and some of the antibiotics could not be used in the future due to their 100% resistancy on all specimens.